2017
DOI: 10.1248/bpb.b17-00221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Galectin-2–Mucin Interaction and Possible Formation of a High Molecular Weight Lattice

Abstract: Galectins comprise a group of animal lectins characterized by their specificity for β-galactosides. Galectin-2 (Gal-2) is predominantly expressed in the gastrointestinal tract and has been identified as one of the main gastric mucosal proteins that are proposed to have a protective role in the stomach. As Gal-2 is known to form homodimers in solution, this may result in crosslinking of macromolecules with the sugar structures recognized by Gal-2. In this study, we report that Gal-2 could interact with mucin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Since Gal‐2 was identified in a screen of mouse gastric mucosal proteins that are uniquely sensitive to S‐nitrosylation , S‐nitrosylation of the sulfhydryl group of C57 may be important for maintaining the function of mGal‐2 in the oxidizing environment of the gastrointestinal tract. Recently, we reported that Gal‐2 could interact with mucin, an important component of gastric mucosa, in a β‐galactoside‐dependent manner and suggested that Gal‐2 plays a role in the gastric mucosa by strengthening the barrier structure through cross‐linking the mucins on the mucosal surface . It has been proposed that galectin‐3 interacts with the O‐glycans of mucins and forms a highly organized and protective cell surface lattice barrier on the apical glycocalyx of ocular surface epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…Since Gal‐2 was identified in a screen of mouse gastric mucosal proteins that are uniquely sensitive to S‐nitrosylation , S‐nitrosylation of the sulfhydryl group of C57 may be important for maintaining the function of mGal‐2 in the oxidizing environment of the gastrointestinal tract. Recently, we reported that Gal‐2 could interact with mucin, an important component of gastric mucosa, in a β‐galactoside‐dependent manner and suggested that Gal‐2 plays a role in the gastric mucosa by strengthening the barrier structure through cross‐linking the mucins on the mucosal surface . It has been proposed that galectin‐3 interacts with the O‐glycans of mucins and forms a highly organized and protective cell surface lattice barrier on the apical glycocalyx of ocular surface epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, local galectin concentrations may be high at infection sites because the galectins are locally secreted by cells as they are being destroyed by infection (Sato et al 2009). Under physiological conditions, Gal-2 may collaborate with other proteins such as mucin (Tamura et al 2017) which is important in host defense against parasitic nematodes (Hasnain et al 2013). This cooperation could enhance Gal-2 activity against C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Lgals2 is predominantly expressed in the gastrointestinal tract and has been identified as one of the main gastric mucosal proteins proposed to have a protective role in the stomach by interacting with mucins (111). In addition, immune functions of Lgals2 have been proposed including its ability to induce apoptosis in activated CD8 + T-cells and its effects on monocytes (112, 113).…”
Section: Galectin-2 (Lgals2)mentioning
confidence: 99%